2010
DOI: 10.1111/j.1365-2486.2009.02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the carbon fluxes of a vegetated drained lake basin chronosequence on the Alaskan Arctic Coastal Plain

Abstract: Greenhouse gas fluxes from vegetated drained lake basins have been largely unstudied, although these land features constitute up to 47% of the land cover in the Arctic Coastal Plain in northern Alaska. To describe current and to better predict future sink/source activity of the Arctic tundra, it is important to assess these vegetated drained lake basins with respect to the patterns of and controls on gross primary production (GPP), net ecosystem exchange, and ecosystem respiration (ER). We measured CO 2 fluxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
101
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 67 publications
13
101
1
Order By: Relevance
“…The improved performance when including VIs in this study is especially useful in regards to monitoring plant productivity and ecosystem functioning. It has been shown previously [82,83] that NDVI can be linked heavily with net ecosystem exchange (NEE) [84,85] and CH 4 fluxes [25] for example. NDVI can be highly correlated with vegetation leaf area index (LAI), but also is invariant at higher LAI ranges and can be very sensitive to background variations in vegetation communities such as background soil and water [8].…”
Section: Discussionmentioning
confidence: 99%
“…The improved performance when including VIs in this study is especially useful in regards to monitoring plant productivity and ecosystem functioning. It has been shown previously [82,83] that NDVI can be linked heavily with net ecosystem exchange (NEE) [84,85] and CH 4 fluxes [25] for example. NDVI can be highly correlated with vegetation leaf area index (LAI), but also is invariant at higher LAI ranges and can be very sensitive to background variations in vegetation communities such as background soil and water [8].…”
Section: Discussionmentioning
confidence: 99%
“…Bryophytes represent between 60 and 95 % of the overall live biomass in similar wet meadow communities , with much of the variation due to small-scale heterogeneity associated with micro-topography Hollister and Flaherty, 2010). Across the BE drained lake bed, mosses represent most of the live above-ground biomass (Zona et al, 2009(Zona et al, , 2010(Zona et al, , 2011. Up to 60 % of the ecosystem's net daytime CO 2 uptake at the end of the growing season at BE is represented by Sphagnum (Zona et al, 2011).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Additionally, over time, basin productivity decreases as wet graminoid vegetation communities, including productive grass (Calamagrostis and Dupontia) and sedge fens (Carex aquatilis), are replaced by ericaceous bog and tussock-dominated ecosystems. Zona et al [32] have shown very high Gross Primary Productivity (GPP) for graminoid vegetation of younger DTLBs compared to the vegetation community of older DTLBs in Arctic ecosystems. This vegetative succession occurs as nutrients from the fresh lake sediments are consumed, permafrost aggradation causes limitations in rooting depth and liquid water availability, and ground ice formation and frost heave result in surface drying [10,32].…”
Section: Introductionmentioning
confidence: 99%
“…Zona et al [32] have shown very high Gross Primary Productivity (GPP) for graminoid vegetation of younger DTLBs compared to the vegetation community of older DTLBs in Arctic ecosystems. This vegetative succession occurs as nutrients from the fresh lake sediments are consumed, permafrost aggradation causes limitations in rooting depth and liquid water availability, and ground ice formation and frost heave result in surface drying [10,32]. Over time, low-centered ice wedge polygons start to develop in drained basins, indicating the accumulation of massive ground ice bodies [33], which eventually creates preconditions for new ponding and the beginning of a new thermokarst lake cycle [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation